The 3D vase museum: a new approach to context in a digital library - Shiaw, Horn-yeu; Jacob, Robert J. K.; Crane, Gregory R. (Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries, 2004)
We present a new approach to displaying and browsing a digital library collection, a set of Greek vases in the Perseus digital library. Our design takes advantage of three-dimensional graphics to preserve context even while the user focuses in on a single item. In a typical digital library user interface, a user can either get an overview for context or else see a single selected item, sacrificing the context view. In our 3D Vase Museum, the user can navigate seamlessly from a high level scatterplot-like plan view to a perspective overview of a subset of the collection, to a view of an individual item, to retrieval of data associated with that item, all within the same virtual room and without any mode change or special command. We present this as an example of a solution to the problem of focus-plus-context in information visualization. We developed 3D models from the 2D photographs in the collection and placed them in our 3D virtual room. We evaluated our approach by comparing it to the conventional interface in Perseus using tasks drawn from archaeology courses and found a clear improvement Subjects who used our 3D Vase Museum performed the tasks 33% better and did so nearly three times faster.